2019
DOI: 10.1039/c9nr04726c
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer SnP3: an excellent p-type thermoelectric material

Abstract: Monolayer SnP3 is a novel two-dimensional (2D) semiconductor material with high carrier mobility and large optical absorption coefficient, implying its potential applications in the photovoltaic and thermoelectric (TE) fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
104
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(112 citation statements)
references
References 77 publications
2
104
0
3
Order By: Relevance
“…2D layered materials, such as single layer graphene [16][17][18] , silicene 19,20 , phosphorene 21,22 , borophene 23,24 , and a series of other layered materials [25][26][27] , have been systematically investigated in scientific community for using as TE materials. Recently, 2D triphosphides are reported one after another with fascinating properties, raising great concern 28,29 .…”
Section: Introductionmentioning
confidence: 99%
“…2D layered materials, such as single layer graphene [16][17][18] , silicene 19,20 , phosphorene 21,22 , borophene 23,24 , and a series of other layered materials [25][26][27] , have been systematically investigated in scientific community for using as TE materials. Recently, 2D triphosphides are reported one after another with fascinating properties, raising great concern 28,29 .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, some previous studies have indicated that the electron-phonon coupling can severely affect the electron transport properties such as spin filter and magnetoresistances (Liu et al, 2017b;Li and Chen, 2017). Again, (Zhu et al, 2019) found that the presence of bipolar effect in SnP 3 could lower the system thermal conductivity and help enhance the ZT value (∼3.4). Hence, new theoretical method including multiparticle coupling is necessary to predict the thermoelectric performance of nanostructurs.…”
Section: Thermoelectric Conversionmentioning
confidence: 94%
“…For example, Ouyang et al (2018) predicted the ZT value up to 2.06 along the armchair direction of InP 3 monolayer at room temperature. Zhu et al (2019) indicated that the ZT value of monolayer SnP 3 was 3.46 along the armchair direction at 500 K. Single-layer SbP 3 (Sun et al, 2020) and GeP 3 (Jing et al, 2017) are also predicted as good TE materials.…”
Section: Introductionmentioning
confidence: 92%